Caracterização do meio físico da bacia do córrego caçula e processos de degradação associados com vistas ao planejamento territorial - Santos, Franciane Mendonça dos [UNESP] (2014)
Natural resources use grows in human society in quantitative and qualitative ways. Environmental degradation processes usually becomes from soil degradation, particularly erosion. Managing its processes demands environmental knowledge and understanding the relationships between natural attributes, whose is a very difficult target. Environmental studies that allows these processes understanding demands very detailed studies, whose were expensive and slow. These Project intents to develop environmental studies in Córrego Caçula Basin based on digital cartography methods resulting low cost and agile surveys. Characterization of the physical environment of the watershed was based on the Pejon Zuquette (1993) methodology, the tools of ArcHydro, the curve-number method developed by the Soil Conservation Service -. SCS and methodology of Soares et al. (2012) for determination of the potential runoff and infiltration potencial with the attributes of the relief obtained from Topodata, and other attributes of the physical environment (CONSÓRCIO INTERMUNICIPAL PARA O DESENVOLVIMENTO DA IRRIGAÇÃO NA REGIÃO DE URUBUPUNGÁ- CINDIRU-CINDIRU, 1995; LOLLO, 1998). These methodologies enabled the discussion of the effectiveness of approaches to evaluate the potential occurrence of degradation processes (erosion and sedimentation) in the area. To complement these analyzes was determined susceptibility to erosion and limitations for the use and occupation in order to identify areas most susceptible to degradation processes and establish the potential and limitations of territorial planning area. The use and occupation of land in the study area for the years 2001 and 2009, from satellite images, enabled us to verify the usage scenario and past and current occupation as well as the influence of this modification on the degradation processes. This characterization process expeditiously and cost resulted in an alternative to characterize the natural ...